Parents’ Knowledge About First Molar Teeth Caries at MI H Ruqoiyah Sidoarjo 2025 - Adawiyah, Robiatul; Edi, Imam Sarwo; Larasati, Ratih (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Introduction: The prevalence of caries or cavities continues to decline in developed countries, while dental caries tends to increase in developing countries considering the high rate of dental caries requires optimal treatment, especially to prevent caries in children. Problem: The problem in this study is the high rate of permanent first molar tooth caries in children in grades 4 and 5 of MI H Ruqoiyah. Objective: The purpose of this study was to determine the description of parental knowledge about permanent first molar tooth caries in grades 4 and 5 at MI H Ruqoiyah Taman Sidoarjo school. Method: The descriptive research method targeted parents of students in grades 4 and 5 at MI H Ruqoiyah Sidoarjo, the study was conducted from September 2023 to February 2025, the data collection method was by filling out a questionnaire. The data collection procedure was by giving questionnaire sheets to parents. Data analysis using percentages and tables. Result: The results of this study indicate that the knowledge of parents of students in grades 4 and 5 is in the sufficient category.